In vitro Antibacterial Activity of Mentha spicata Essential Oil against Some Pathogenic Bacteria - Sara I. Othman; Fouad H. Kamel (Polytechnic Journal)
Mentha spicata (M. spicata) is within family Lamiaceae that spreads mainly in the temperate and subtemperate zones of the world. It is considered as a good source of essential oils (EOs), which is widely used in food production and pharmaceutical industries. The aim of the current study is to evaluate antibacterial activities associated with the EO of M. spicata cultivated in Iraq-Erbil city. The aerial parts of M. spicata were subjected to hydro distillation to extract the oil. Antimicrobial potential was tested against many microorganisms, signifying Gram-negative and Gram-positive bacteria. EO of M. spicata demonstrated antimicrobial activities with best susceptibility observed for Gram-negative bacteria toward the oil. The results suggest that EO of M. spicata may have potential value as antibacterial activities.